Marketability and Financial Performance of Suyac Mangrove Eco-Park - Mate, Nince L.; Estores, Kristin Iris G. (Philippine Social Science Journal, 2020)
Ecotourism has shown significant fast-paced growth and is recently getting tremendous attention in the world. However, there are many challenges in product development and marketing. Suyac Mangrove Eco-Park needs the right marketing research for its community-based ecotourism development for people’s welfare, especially the community and the tourists. Hence, the study assesses the level of marketability in terms of 7P’s marketing mix and financial performance of Suyac Mangrove Eco-Park. Likewise, this study sought if a significant difference exists in the level of marketability when respondents are grouped according to designation.